Boundary Value Problems Arising in Kalman Filtering - Bashirov, Agamirza; Mazhar, Zeka; Ertürk, Sinem (Springer International Publishing, 2008)
The classic Kalman filtering equations for independent and correlated white noises are ordinary differential equations (deterministic or stochastic) with the respective initial conditions. Changing the noise processes by taking them to be more realistic wide band noises or delayed white noises creates challenging partial differential equations with initial and boundary conditions. In this paper, we are aimed to give a survey of this connection between Kalman filtering and boundary value problems, bringing them into the attention of mathematicians as well as engineers dealing with Kalman filtering and boundary value problems. Copyright (c) 2008 Agamirza Bashirov et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
The file in this item is the publisher version (published version) of the article.
Keywords: Difference and Functional Equations, Partial Differential Equations; Approximations and Expansions, Analysis, Ordinary Differential Equations; Mathematics, general, APPLIED, Noise, Studies; Mathematical models, Economic models, Science, QA1-939